Impact of ground size on meat quality and meat products: a review - Abdul, Mustapha; Kumar, Pavan; Mohammad Rashedi, Ismail Fitry; Mohd Zaki, Nor Nadiha; Arshad, Syariena; Ishak, Iskandar; Sazili, Awis Qurni (Informa Healthcare, 2025)
Minced meat is a crucial and widely accepted ingredient used in the preparation of various foods that are widely consumed worldwide. Because of its versatility and handiness, it is used in various dishes, such as emulsion-based meat products, meatballs, sausages, patties, and hamburgers. The ground size has a significant effect on the meat quality attributes. Based on ground size, minced meat can be categorized into three types, viz., fine, medium, and coarse. The present work critically reviewed the impact of ground size on the various quality attributes of meat and meat products. The different ground sizes obtained as a result from different processing methods (such as by using a mincer, grinder, or knife) had a significant impact on the meat quality attributes, including juiciness, flavor, color, pH, tenderness, and sensory evaluation. However, the changes in the meat quality parameters are not only caused by the intensity of the mincing/grinding or the amount of non-intact cells (ANIC), but also by the breakdown of the muscle fibers, structure loss, connective tissues, myofibrillar proteins, and exposure of the surface area. The results of the study revealed that mincing sizes influence the quality parameters such as textural integrity, WHC, color, juiciness, and pH.